How do you find the asymptotes for # y= (x+1)^2 / ((x-1)(x-3))#?

1 Answer
Mar 7, 2016

Answer:

Vertical Asymptotes: #x=1,3#
Horizontal asymptotes:#y=1#

Explanation:

To find the vertical asymptotes take the denominator and set it equal to 0 and solve for x.
To find the horizontal asymptote find the limit as x goes to infinity in both directions so we use the end behavior rule and take the highest degree term from the top which will be #x^2# and the highest degree term from the bottom which is also #x^2# and divide them. Hence y=1 is the horizontal asymptote.